Curriculum Reform of Disaster Prevention and Control Based on the Integration of Innovation and Entrepreneurship - Zhang, Junxiang; Chen, Liang; Qu, Lina (International Journal of Social Sciences and Public Administration, 2024)
Innovative and entrepreneurial talents is the main driving force for local universities to promote the smooth development of the society, and is also a key factor in improving the employment rate of graduates. Using the example of undergraduate safety engineering students, this study analyzed the important role that the innovative and entrepreneurial talents of students play in the society development. The current problems in teaching are analyzed in terms of theoretical teaching, practical teaching, lack of practical ability of the teaching staff and assessment methods. In order to solve the above problems, this study constructed a multidisciplinary cross-fertilization teaching system in theoretical and practical teaching, and proposes a diversified evaluation method, and applying them to teaching practice with some success. To cultivate talents with innovative thinking and skills, and to provide a reference for the cultivation of high-quality applied talents in China’s security engineering profession.